Public Participation and Local Government Readiness in Building Function Certificate (SLF) Services: a Comparative Study of Malang Regency and Batu City - Bambang Diana; Dwi Putranto Riau; Amud Sunarya (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2026)
This study aims to analyze community participation and local government readiness in the management of Building Functionality Certificates (SLF) through the Building Management Information System (SIMBG), using a comparative multiple-case study approach in Batu City and Malang Regency.The research applies a qualitative method with data collected through in-depth interviews, focus group discussions (FGDs), observation, and documentation. A total of 11 informants were involved, consisting of representatives from local government agencies (DPUPR and DPMPTSP), as well as building owners/applicants and technical consultants to ensure balanced perspectives.The findings reveal that community participation has increased gradually due to digital service expansion and active socialization programs. However, participation remains constrained by limited public literacy, complex technical requirements, and system disruptions in SIMBG. Meanwhile, local government readiness is reflected in adaptive service strategies such as mobile services, technical assistance, and offline alternatives during system failures.The comparative analysis shows that Batu City emphasizes adaptive outreach strategies due to geographical challenges, while Malang Regency focuses on service stability and institutional efficiency. The study highlights that digital public services (SIMBG) simultaneously enhance access but also introduce new administrative challenges.This research contributes to the development of digital public service governance and participatory policy implementation, emphasizing the importance of collaboration between government, communities, and stakeholders in achieving safe and sustainable building management.